2022
DOI: 10.26554/sti.2022.7.2.257-262
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Liquid Smoke from Shorea pachyphylla using Response Surface Methodology and its Characterization

Abstract: The present study aims to optimize the processing variables producing liquid smoke from mabang wood (Shorea pachyphylla) by using Response Surface Methodology (RSM). In this investigation, a design of experiment with different combinations of pyrolysis temperature and pyrolysis time on the liquid smoke yield from mabang wood was applied. The response of the optimal yield, temperature, and time of pyrolysis was predicted using a mathematical model. The optimal operating conditions for the process of yielding 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…where Y denotes the expected response; 𝛽 0 denotes the constant regression coefficients; 𝛽 𝑖 , 𝛽 𝑖𝑖 , and 𝛽 𝑖𝑗 are the coefficients of linear, quadratic, and interaction effects; the variable codes are denoted by 𝑥 𝑖 and 𝑥 𝑗 ; and ɛ is the error (Oramahi, Kustiati, & Wardoyo, 2022).…”
Section: Optimization Using Response Surface Methodologymentioning
confidence: 99%
“…where Y denotes the expected response; 𝛽 0 denotes the constant regression coefficients; 𝛽 𝑖 , 𝛽 𝑖𝑖 , and 𝛽 𝑖𝑗 are the coefficients of linear, quadratic, and interaction effects; the variable codes are denoted by 𝑥 𝑖 and 𝑥 𝑗 ; and ɛ is the error (Oramahi, Kustiati, & Wardoyo, 2022).…”
Section: Optimization Using Response Surface Methodologymentioning
confidence: 99%
“…Empty bottles are weighed, filled with liquid smoke, and then weighed again, compared to the weight of the initial raw material before undergoing pyrolysis. Yield is an essential parameter for knowing the results of a process [7].…”
Section: Liquid Smoke Yieldmentioning
confidence: 99%
“…Smoke powder is the result of the encapsulation process of maltodextrin into liquid smoke as a coating medium, so it has a higher phenol content than liquid smoke and can maintain food products, especially the quality and durability of meatballs [13]. Several studies reported that smoke powder is useful for inhibiting bacterial growth, as well as maintaining the quality of food products [18][19][20]. Until recently, however, only a few studies on the application of smoke powder as a meatball preservative have been carried out.…”
Section: Introductionmentioning
confidence: 99%